THE DETERMINING FACTORS OF STUDENT INTENTION TO DONATE IN SOCIAL CROWDFUNDING MEDIA - Manggarani, Cynthia Ayu; Ahmad, Zulfikar Ali (Hasanuddin Economics and Business Review, 2020)
The issue of social crowdfunding has been widely discussed in various countries. In Indonesia, social crowdfunding media platforms are frequently used for social activities such as the donation for the victims of natural disasters or donation for people who suffer from financial deficiency. However, empirical research on social crowdfunding is finite. Even though the platform has been extensively used by the society, the lack of interest towards study in social crowdfunding is evident due to the obscureness of government regulations regarding the fundraising media. Considering the enormous contribution of social crowdfunding media for the people in need, the enthusiasm of the society to participate in the donation activities thus need to be elevated. This study aims to determine the degree of one’s motivation in trying to try to donate through social crowdfunding media. The data of this research was collected using survey method with a total of 300 respondents.